Jane Hicks Gentry : A Singer Among Singers - Smith, Betty N. (Book collections on Project MUSE., 1998)
""Winner of the North Carolina Society of Historians Award Jane Hicks Gentry lived her entire life in the remote, mountainous northwest corner of North Carolina and was descended from old Appalachian families in which singing and storytelling were part of everyday life. Gentry took this tradition to heart, and her legacy includes ballads, songs, stories, and riddles. Smith provides a full biography of this vibrant woman and the tradition into which she was born, presenting seventy of Gentry's songs and fifteen of the ""Jack"" tales she learned from her grandfather. When Englishman Cecil Sharp.